Analisis Buku Nahwu Wadhih Juz 2 Karya Ali Al-Jarimi dan Musthafa Amin - Akmal Walad Ahkas; Al Lu’lu’ Mahabbah Fillah (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2022)
This study aims to analyze: 1) to find out the history of Nahwu Wadhih Juz 2 book by Ali Al-Jarimi and Musthafa Amin. 2) to find out the purpose of the Nahwu Wadhih Juz 2 book by Ali Al-Jarimi and Musthafa Amin. 3) to find out the advantages and disadvantages of the Nahwu Wadhih Juz 2 book by Ali Al-Jarimi and Musthafa Amin. This research is a type of research that is library research and is descriptive analysis. The results showed that: 1) the Nahwu Wadhih book was written by 2 great scholars in Egypt, namely Dr. Ali Al-Jarimi and Dr. Musthafa Amin and this book was first printed in 1983 M/1403 H. 2) the purpose of the Nahwu Wadhih book is to bring beginners closer to learning Arabic in an accurate way. This book is used in a number of pesantren and other Islamic religious schools, especially in modern-based pesantren. 3) Nahwu Wadhih Juz 2 book by Ali Al-Jarimi and Musthafa Amin. This book has several advantages, but is also not free from shortcomings.